Perceptions and practices of principals: examining instructional leadership for curriculum reform - Ralebese, Moeketsi David; Jita, Loyiso Currell; Badmus, Olalekan Taofeek (Frontiers in Education, 2025)
A theoretical and empirical grounded explanation is constructed on how primary school principals perceive and enact instructional leadership during curriculum reform. This study used a concurrent mixed-methods design to integrate data from 248 survey responses with insights from in-depth interviews and observations of three school principals. Findings indicate that while principals perceive themselves as actively engaged in instructional leadership, particularly through Principal Instructional Management dimensions in defining school missions, managing instructional programs, and fostering positive school climate—gaps exist between their self-perceptions and enacted practices. Thematic analysis shows that principals influence the establishment of school goals, facilitate instructional collaboration, and reinforce positive behaviors among teachers and learners. However, inconsistencies emerge in data-driven decision-making and direct instructional oversight. Role Perception and enactment in this study demonstrate how personal beliefs, contextual constraints, and systemic challenges influence leadership behaviors in schools. This study exposes the need for structured training, clearer role expectations, and sustained support to enhance principals’ leadership effectiveness. This study contributes to the global discourse on instructional leadership in developing and under-resourced contexts, offering insights for policymakers and educational stakeholders on strengthening leadership frameworks for sustainable curriculum reform.